A First Step up the Energy Ladder? Low Cost Solar Kits and Household's Welfare in Rural Rwanda - Michael Grimm; Anicet Munyehirwe; Jörg Peters; Maximiliane Sievert (Institute for the Study of Labor (IZA), 2014)
More than 1.3 billion people lack access to electricity. The UN have proclaimed the goal of providing electricity to all by 2030. In recent years, Pico-Photovoltaic kits have become a lower cost alternative to investment intensive grid electrification. Using a randomized controlled trial we examine uptake and impacts of a simple Pico-Photovoltaic kit that barely exceeds the benchmark of what the UN considers as modern energy. We find significant effects on households' budget, productivity and convenience. Despite these effects, the data shows that adoption will be impeded by affordability, suggesting that policy has to consider subsidized dissemination strategies.
Keywords: O13; O18; Q41; 330; energy access; household technology adoption; Sub-Saharan Africa; randomized controlled trial